Mental health specialist video consultations versus treatment as usual in patients with depression or anxiety disorders in primary care: study protocol for an individually randomised superiority trial (the PROVIDE-C trial) - Haun, Markus W.; Tönnies, Justus; Krisam, Regina; Kronsteiner, Dorothea; Wensing, Michel; Szecsenyi, Joachim; Vomhof, Markus; Icks, Andrea; Wild, Beate; Hartmann, Mechthild; Friederich, Hans-Christoph (Trials, 2021)
Most people with mental disorders, including those with severe and chronic disorders, are treated solely by their general practitioner (GP). Nevertheless, specialised mental health care may be required for specific patients. Notably, the accessibility of mental health specialist care is mainly complicated by (a) long waiting times for an appointment with specialists, (b) long travel distances to specialists, particularly in rural and remote areas, and (c) patients’ reservations about mental health specialist care (including fear of being stigmatised by seeking such care). To mitigate those barriers, technology-based integrated care models have been proposed. The purpose of this study is to examine the effectiveness and cost-effectiveness of a mental health specialist video consultations model versus treatment as usual in patients with depression or anxiety disorders in primary care.
Gesehen am 01.03.2022